(untitled) (American Journal of Islam and Society, 2001)
Transformative inquiry is proposed in this paper as an alternative research method that emerges from the Islamic paradigm and leads to the creation of Islamic knowledge on one hand and inner self transformation on the other. The emphasis, however, will be on transformative research methods based on this union of inner experiences of awakening of the soul from inside and unfolding of research experiences and knowledge from outside. Before doing that, I will shed some light on related issues of conventional and alternative paradigms such as positivism and constructivism. Also related issues to transformation, such as wholeness and relationships, are discussed. Finally, four methods of inquiry, are proposed as transformative methods that have the potential for producing Islamic knowledge.